Examining the Post-operative Well-Being of Women Who Underwent Mammoplasty: A Cross-Sectional Study - Ranieri, Jessica; Fiasca, Fabiana; Guerra, Federica; Perilli, Enrico; Mattei, Antonella; Di Giacomo, Dina (Frontiers in Psychiatry, 2021)
Background. Mammoplasty is the most common surgery used for breast augmentation (aesthetic plastic) and breast reconstruction (disease-related plastic) in women who have been diagnosed with and surgically treated for regional breast cancer with Modified Radical Mastectomy. This study aims to examine the long-term effects of mammoplasty on the psychological well-being of women. Methods. Participants were 44 women aged 30–50 years (mean = 40.4  5.9). They were divided into two groups based on the purpose of the breast surgery they underwent (augmentation surgery [AS] vs. reconstruction surgery [RS]) and the time that had elapsed since their surgery (≤ 3 years vs. > 3 years). Results. Our findings suggest that women who underwent AS reported a decline in their psychological well-being over time. The women who had undergone AS ≤ 3 and > 3 years did not show any differences in emotional functioning, with the exception of the BREAST-Q scores on the satisfaction with breasts subscale. We examined the impact of mammoplasty on the satisfaction levels and well-being of women who had undergone RS (after MRM). They were less satisfied with their breasts than those who belonged to the AS group, confirming our hypothesis. However, this was true only among those who had undergone surgery ≤ 3 years earlier. Conclusions. In conclusion, our findings underscore the need to provide psychological support to those who have undergone breast AS and RS. Additionally, this study implies the need for personalised psychological interventions to improve the emotional adaptation process and enhance women’s mental well-being.